Optimisation of selected plasticiser compounds adsorption on calcium-carboxylate-based linker (Ca-H2BDC) using response surface methodology - Jori Roslan, Muhammad Qusyairi; Aris, Ahmad Zaharin; Razak, Muhammad Raznisyafiq; Mohd Zaki, Muhammad Rozaimi; Mohd Basyaruddin, Abdul Rahman; Lim, Hong Ngee; Mohd Isa, Noorain; Mohamad Roslan, Muhamad Aidilfitri (Elsevier, 2024)
Addressing environmental pollution caused by endocrine disruptor compounds (EDCs), such as plasticisers, has become crucial for public authorities to ensure sustainable development. This study focused on optimising the removal of selected plasticiser compounds from aqueous solutions using a calcium-carboxylate-based linker (Ca-H2BDC). A central composite design (CCD) with four centre points was employed to optimise the process variables, including the concentration of the plasticiser solution, Ca-H2BDC dosage, contact time, and solution pH, with the adsorption removal rate (%) as the response measured. Optimal conditions for removing the selected plasticisers were identified: plasticiser concentration of 5 μg/L, adsorbent dosage of 40 mg, solution pH of 7, and contact time of 60 min. Analysis of variance confirmed the reliability of these conditions, with correlation coefficients (R2 and R2adj) of 0.986 and 0.972 for BPA, 0.977 and 0.955 for BPF, and 0.998 and 0.997 for PFOA, respectively. These conditions resulted in removal capacities of 354.75 mg/g for BPA, 413.23 mg/g for BPF, and 387.98 mg/g for PFOA. Furthermore, response surface analysis revealed a significant mutual effect of contact time and dosage, initial concentration, and pH on BPA, BPF, and PFOA removal efficiency, respectively. A quadratic model for the removal of the selected plasticisers was proposed, in which an economically based experiment was conducted by reducing the contact time to 40 min and the adsorbent dosage to 30 mg. The experiment demonstrated that the removal rate and capacity achieved were <9 % lower than those achieved under the optimised conditions, indicating reliable efficiency. © 2024 Elsevier Ltd